Improving the water supply pumping station operation. - Hrabko, V. V.; Moshnoriz, M. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper considers the issue of power resource efficiency. The objective of the paper is to choose the most efficient operating mode of pumping water-supply station. The task is to find the operating characteristics of each pumping unit under the optimum consumption of electric energy and ensuring the water supply in the city. The optimization is executed with the application of the methods of the mathematical programming of linear and nonlinear types.